Probing the nature of dark matter with deep XMM‐Newton observations of the dwarf spheroidal galaxies1. Issue 2 (22nd March 2017) - Boyarsky, A.; Ruchayskiy, O.
Abstract : We report the results of the very large program with XMM‐Newton (AO‐14) devoted to deep observation of Draco dwarf spheroidal galaxy. The p‐n junction (PN) camera shows a positive spectral feature at E = 3.54 ± 0.06 with a 2.3 σ significance. The two Metal Oxide Semi‐conductor (MOS) cameras show less‐significant or no positive deviations, consistently within 1 σ with PN. These results put the bound on the lifetime of a decaying dark matter particle τ > (7 − 9) × 10 27 s at 95% CL. The spread in this result comes from the uncertainty in the column density of dark matter in the direction of Draco. This limit is consistent with dark matter interpretation of the 3.5 keV line observed in the stacked galaxy clusters, M31 and the galactic center within their 1 − 2 σ uncertainties.